Pelaksanaan Pemeriksaan Tindak Pidana Dengan Acara pemeriksaan singkat - Lubis, Muhammad Ridwan (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2024)
The implementation of criminal examinations using a short examination procedure is only carried out in cases of crimes or violations which do not include minor crimes, which according to the Public Prosecutor, the proof and application of the law is easy and simple in nature. In accordance with the provisions of Article 203 paragraph (1) of the Criminal Procedure Code, those examined according to the short examination procedure are cases of crimes or violations which do not fall under the provisions of Article 205 and which according to the public prosecutor, the proof and application of the law is easy and simple in nature. During a brief examination, the defendant's rights are still taken into account, such as the right to be immediately tried by the Court (Article 50 paragraph (3), the right to be informed clearly in a language he understands about what he is accused of (Article 51 letter b), the right to give information in a clear manner. free to the judge (Article 52). Based on this conclusion, the author suggests that the judge who examines the brief examination proceedings wisely and tactfully pays attention to judicial principles and considers the interests of the parties to the dispute, so that a simple, fast and low-cost trial can be achieved. Therefore, it is recommended that the judge who examines the brief examination proceedings wisely and tactfully pays attention to the principles of justice and considers the interests of the parties to the dispute, so that a simple, fast and low-cost trial can be achieved.Keywords: Examination, Crime, Short Examination Procedure.